The RESISTANCE TRAINING EFFECT ON IGF1 LEVEL OF SARCOPENIA - Komala Sari, A A Ayu Tri Bhuana; Masrani, Nanang; Saraswati, Ni Ketut Rake Putri; Lestari, Putu Dyah Agustina; Rahasbistara, Made Rendra Wisnu; Wahyuni, Nila; Adiatmika, I Putu Gede (Sport and Fitness Journal; Vol 10 No 2 (2022): Volume 10, No. 2, May 2022DO - 10.24843/spj.2022.v10.i02.p04, 2022)
ABSTRACT Aging is something that definitely happens and we can't avoid it but we can prevent it. The quality and quantity of muscle mass decreases with age. Sarcopenia is a decrease in muscle mass accompanied by a decrease in muscle strength. Muscle metabolism is influenced by many factors and signaling pathways. The level of IGF-1 plays an important role in maintaining the quality of skeletal muscle. Recent studies have shown that resistance training is essential for muscle development and increasing the efficiency of agonist and antagonist muscle groups. However, research on this topic varies greatly in terms of the frequency, intensity, duration, and type of exercise that builds IGF-1. The study was conducted using the literature method. We reviewed and compared the most recent journals discussing the relationship between sarcopenia and regular long-term physical exercise. Physical exercise with resistance training showed significant results for muscle strength and muscle mass in the elderly. High-resistance training has a major effect on increasing GH and cortisol. In conclusion, certain physical activities have a positive effect on muscle health that can be withdrawn by IGF1. Keywords: Sarcopenia; IGF-1; Resistance training